Das arztrechtliche System als Grenze der arbeitsteiligen Medizin zugleich ein Beitrag zur privatrechtsdogmatischen Integration des Arztrechts - Ballhausen, Benedikt (Universitätsverlag Göttingen, 2013)
Modern medicine is increasingly characterised by the division of labour. Therefore, this process as well as the concepts of delegation and substitution need to be clarified on a juridical basis. Accordingly, this dissertation is an approach to answer relevant questions of medical law, such as: Which concrete medical processes can be carried out based on the division of labour without risking legal steps regarding liability or pay to be taken? Based on distinct principles of medical law, the author thus develops a systematic framework for the division of medical labour. In this regard, an applicable and simultaneously docmatically substantiated method is focussed.